Factor Associated with Diabetes Burnout Syndrome Among Type 2 Diabetes Mellitus - Nian Afrian Nuari (STIKes Patria Husada Blitar, 2020)
Diabetes mellitus is a metabolic disease that is often found in Indonesia and the number of sufferers is increasing every time. Management of therapy patients with type 2 diabetes mellitus consists of five steps that require compliance and discipline to maintain stable blood sugar levels. This condition causes burnout by diabetes mellitus patients. The purpose of this study was to identify factors associated with diabetes mellitus among type 2 Diabetes mellitus. This study used a correlational design with a cross-sectional approach with a sample size of 89 respondents who were taken by purposive sampling. Based on the results of the study it was found that most Diabetes mellitus patients were 56-60 years old, female, and the education background was junior high school level. The level of income of majority of the respondents was under 1 million rupiahs andÂ suffered from Diabetes mellitus for 1-10 years. The result found almost the entire entire patient consumed diabetes drugs. Most of the respondents had a severe category in diabetes burnout syndrome. The research found that there was a correlation between age, gender educational background, level of income, duration suffering DM, consumption of diabetes drugs with diabetes burnout syndrome among type 2 Diabetes Mellitus. Health workers must provide education about the importance of preventing the incidence of burnout syndrome and taking therapeutic management for patients who already had diabetes burnout syndrome.